FUN LEARNING BASED ENGLISH COMMUNICATION COMPETENCY TRAINING IN TEACHER WORK GROUP OF OFFICE ADMINISTRATION IN SURAKARTA - M.CHOERUL UMAM; C. DYAH SULISTYANINGRUM INDRAWATI; PATNI NINGHARDJANTI; ANTON SUBARNO; WINARNO; CHAIRUL HUDA ATMA DIRGATAMA (CV KULTURA DIGITAL MEDIA, 2021)
The era of globalization has impacted the economic and technological progress. Information technology developments are running fast, so much needed a concept and learning mechanism of teaching-based information technology packed into the form of digitalization of Method. Based on the preliminary observation and study that most teachers have not been able to create Fun learning-based competence in supporting the quality and success of learning activities. English Competence Training aims to improve the knowledge and skills of teachers in vocational high school in making learning methods more variative and innovative. Results obtained from training are: 1) Improvement of teacher skills in Fun Learning based English competence management 90 %, 2) Improvement of teacher skills in Fun Learning based English competence Implementation 88%, 3) Improvement of teacher performance skills in productivity in creating Fun Learning Based English Competence has reached 88 %.